Study of the eﬀect of COPD on the quality of life of patients according to the results of the Cat - test in outpatient practice - T. M. Levina; M. D. Romanov (Сеченовский вестник)
The article analyzes the impact of chronic obstructive pulmonary disease (COPD) on the quality of life of patients according to the results of clinical and instrumental examination and ante - testing using the integral CAT-test.Objective. Study of the eﬀect of COPD on the quality of life in outpatient practice based on the results of the integral CAT-test. Materials and methods. The article analyzes the impact of chronic obstructive pulmonary disease (COPD) on the quality of life of patients according to the results of clinical and instrumental examination and ante - testing using the integral CAT-test.Results. The primary treatment of patients with a long history of COPD in stages II and III recorded a greater impact of the respiratory component on the quality of life. Because of complex therapy (inhaled bronchodilators and glucocorticosteroids, antibiotics according to indications, non - pharmacological methods of pulmonary rehabilitation, respiratory gymnastics, and school for patients with COPD) during 1 year of follow - up, there were signiﬁcant changes in the indicators of quality of life. In patients with the sum of scores on the SAT-test up to 20 showed a decrease in the number and severity of clinical symptoms of respiratory status, and the average value of forced expiratory volume in 1 s (FEV1) remained almost at the same level with a signiﬁcant improvement in the overall quality of life. In patients with a score of 21 or higher, the FEV1 level after 1 year signiﬁcantly increased by 12.2%, which is apparently due to a higher level of patient compliance and the eﬀect of pulmonary rehabilitation measures.Conclusion. The results of assessing the impact of diﬀerent stages of COPD on the quality of life of patients in outpatient practice will improve the monitoring of the course of the disease and optimize the prognosis, state the eﬀectiveness of complex therapy and adjust the dispensary observation plan.